2012
DOI: 10.1021/ac203446g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Properties of Powders on the Generation and Transmission of Raman Scattering

Abstract: This version is available at https://strathprints.strath.ac.uk/40538/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…20,22,24,[29][30][31][32] The absence of sub-sampling limitations in transmission Raman spectroscopy has been illustrated by numerical simulations 20 and experimental investigations. 20,[33][34][35][36] Matousek and Parker showed that when a 0.5 mm thick inter-layer was moved from the sample surface to a depth of 3 mm within a tablet medium, the simulated backscatter Raman signal decreased by four orders of magnitude. 20 In comparison, numerical 20,34 and experimental [34][35][36] investigations showed that the signal was only weakly dependent on the depth of the inter-layer in transmission mode; a reduction in signal was observed when the inter-layer was located at the sample surface owing to loss of laser and Raman photons at the air-sample interface.…”
Section: Introductionmentioning
confidence: 99%
“…20,22,24,[29][30][31][32] The absence of sub-sampling limitations in transmission Raman spectroscopy has been illustrated by numerical simulations 20 and experimental investigations. 20,[33][34][35][36] Matousek and Parker showed that when a 0.5 mm thick inter-layer was moved from the sample surface to a depth of 3 mm within a tablet medium, the simulated backscatter Raman signal decreased by four orders of magnitude. 20 In comparison, numerical 20,34 and experimental [34][35][36] investigations showed that the signal was only weakly dependent on the depth of the inter-layer in transmission mode; a reduction in signal was observed when the inter-layer was located at the sample surface owing to loss of laser and Raman photons at the air-sample interface.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26] The lower NIR absorbance and Raman intensity observed for the interlayer when positioned at the surface can in both cases be attributed to lower photon density at the air-sample interface, relative to the center of the sample, owing to loss of photons to the air. This results in a reduction in the number of photons absorbed or Raman photons generated and subsequently detected when the interlayer occupies a nearsurface position.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, owing to the recent interest in the use of transmission Raman spectrometry for the analysis of pharmaceutical dosage forms, 20,21 there have been a number of theoretical and experimental studies examining the variation of the transmission Raman signal with depth in turbid media. [22][23][24][25][26] It was suggested in a recent paper that the variation in the transmission Raman signal with depth would also be exhibited by transmission NIR spectrometry. 22 While transmission Raman spectrometry can be employed with non-absorbing and weak to moderately absorbing materials, 22 it is inherent to NIR spectrometry that at least weakly absorbing materials are present to give rise to a signal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the orientation did not significantly affect the BMS-B data set with the ratio of the two measurements being approximately 1 for all the tablets. Townshend et al [16] also performed TRS measurements while flipping the tablets; however, rather than directly comparing the Raman intensity, they studied the photon attenuation coefficient as a function of tablet thickness and determined that attenuation coefficient was not impacted by tablet orientation. In our study, since the ratio of the signals was significantly different for the two materials (BMS-A vs BMS-B), then the tablet orientation should be controlled during analysis.…”
Section: Experiments 2: Effect Of Tablet Orientation (Configuration B)mentioning
confidence: 99%